Recent trends in the transdermal delivery of therapeutic agents used for the management of neurodegenerative diseases. (28th May 2017) - Ita, Kevin
Abstract: With the increasing proportion of the global geriatric population, it becomes obvious that neurodegenerative diseases will become more widespread. From an epidemiological standpoint, it is necessary to develop new therapeutic agents for the management of Alzheimer's disease, Parkinson's disease, multiple sclerosis and other neurodegenerative disorders. An important approach in this regard involves the use of the transdermal route. With transdermal drug delivery systems (TDDS), it is possible to modulate the pharmacokinetic profiles of these medications and improve patient compliance. Transdermal drug delivery has also been shown to be useful for drugs with short half-life and low or unpredictable bioavailability. In this review, several transdermal drug delivery enhancement technologies are being discussed in relation to the delivery of medications used for the management of neurodegenerative disorders.